Learning Outcomes of Appreciation of Malay Folklore Using a Constructivist Approach through Manual Modules - Nasir, Siti Noridayu Abd; Sarimin, Tumisah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Malay folklore has been widely published, allowing it to reach almost all Malay cultural areas that span national borders. One of the Malay folktales is entitled 'Datuk Kaya Montel', which is included in the collection of Riau Islands folklore, 'Patahnya Gunung Daik.' This study aims to describe: 1) the learning outcomes of the appreciation of the Malay folklore 'Datuk Kaya Montel' using a constructivist approach in the manual module; 2) the similarity of the learning outcomes of the appreciation of the Malay folklore 'Datuk Kaya Montel' using the constructivist approach in the manual module per sample group. This descriptive-quantitative study was conducted in 2024 at Sekolah Menengah Kebangsaan Shanbandaraya, Klang, Selangor, Malaysia dan Sekolah Menengah Kebangsaan Laksamana, Kota Tinggi, Johor, Malaysia. The population of this study consisted of grade 5 students who learned to appreciate the Malay folklore 'Datuk Kaya Montel' using the constructivist approach. They numbered 62 students, divided into 32 from Selangor and 30 from Johor. A sample of 54 students was selected using a statistical formula, comprising 28 students from Selangor and 26 students from Johor. Learning outcome data were collected using a multiple-choice test with four options. Learning outcome data were analyzed using parametric inferential statistical procedures, namely a one-sample t-test using an expected mean of 21,18 and an independent sample t-test. The results of the study: 1) the learning outcomes of the appreciation of the Malay folklore 'Datuk Kaya Montel' using a constructivist approach in the manual module were in the very high category; 2) there was no difference in the learning outcomes of the appreciation of the Malay folklore 'Datuk Kaya Montel' using a constructivist approach in the manual module per sample group.